Fires in the wetlands Ramsar Los Pantanos de Villa (Lima, Peru): Advances in their knowledge and future perspectives - Ramirez, Dámaso W. (2018)
Fires have become a recurrent menace to wetlands of the central coast of Peru. However, the scientific knowledge of its impacts is scarce and does not allow adequate prevention measures. This study evaluated the current state of knowledge of fires recorded for wetland Los Pantanos de Villa Wildlife Refuge, as well as the species affected by these events. In the last ten years, four fires have impacted the Pantanos de Villa, affecting 3.51% of the surface of the wetland. The rushes were the plant community most impacted by the fires. We identified 34 species frequently affected by these disturbances, 12 belonging to flora and 22 to fauna, including vulnerable species as well as species new to science. These data show the need to strengthen scientific studies that quantify the effects of fire on the tropical coastal wetland. Finally, we discuss the problem of recurrent fires in this protected area and prevention measures.